An investigation on the drag reduction performance of bioinspired pipeline surfaces with transverse microgrooves - Liu, Weili; Ni, Hongjian; Wang, Peng; Zhou, Yi (Beilstein Journal of Nanotechnology, 2020)
A novel surface morphology for pipelines using transverse microgrooves was proposed in order to reduce the pressure loss of fluid transport. Numerical simulation and experimental research efforts were undertaken to evaluate the drag reduction performance of these bionic pipelines. It was found that the vortex ‘cushioning’ and ‘driving’ effects produced by the vortexes in the microgrooves were the main reason for obtaining a drag reduction effect. The shear stress of the microgrooved surface was reduced significantly owing to the decline of the velocity gradient. Altogether, bionic pipelines achieved drag reduction effects both in a pipeline and in a concentric annulus flow model. The primary and secondary order of effect on the drag reduction and optimal microgroove geometric parameters were obtained by an orthogonal analysis method. The comparative experiments were conducted in a water tunnel, and a maximum drag reduction rate of 3.21% could be achieved. The numerical simulation and experimental results were cross-checked and found to be consistent with each other, allowing to verify that the utilization of bionic theory to reduce the pressure loss of fluid transport is feasible. These results can provide theoretical guidance to save energy in pipeline transportations.
Keywords: bionic pipeline; drag reduction; drag reduction mechanism; fluid transport; transverse micro-grooves